HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KECEMASAN KELUARGA PASIEN THYPOID DI RUANG ANAK RSU DR. MM. DUNDA LIMBOTO - Firmawati Firmawati; Salahuddin Liputo (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Typhoid fever is an endemic disease that is included in the health problems in developing countries, including Indonesia because it can bring the impact of increased morbidity and mortality. Typhoid fever is estimated to strike 22 million people per year with a mortality rate of 200,000 people per year. The purpose of this study was to determine how the relationship of knowledge and attitudes of families with typhoid patient anxiety in the child RSU MM Dunda Limboto Gorontalo district. The method used is a sectional descriptive study, with a total population of 55 families with a sample of 55 families, using consecutive sampling with inclusion criteria questionnaire measuring instrument. Knowledge and the independent variables and the dependent variable is the attitude of anxiety. Analysis of the data in this study using a statistical test